Experience in Transoral Robotic Surgery in Pediatric Subjects: A Systematic Literature Review - Vianini, Matteo; Fiacchini, Giacomo; Benettini, Giacomo; Dallan, Iacopo; Bruschini, Luca (Frontiers in Surgery, 2021)
Pediatric transoral robotic surgery (TORS) improved from 2007 to 2020, widening its indications and feasibility. The aim of this work is to systematically analyze the procedures performed from the first use until the current year, observing their evolution over time. A systematic literature review was performed using PubMed, Scopus, Web of Science, and Cochrane databases between 1st March 2000 and 1st April 2020. We selected only English-written studies and studies performed in live human subjects. 16 studies were found with a total of 73 subjects treated, 41 males and 32 females with an average age of 6.8 +/- 4.99 years. There have been 4 (5.47%) conversions. Both functional and benign-malignant diseases have been treated in the series. 11 (15.06%) pre-operative tracheostomy and zero post-operative tracheostomies. The bleeding data was only reported in 9 studies and was less than 50 ml. Only one (1.36%) intra-operative complication and 10 (12.32%) postoperative complications were reported. We consider the TORS procedures in pediatric subjects up to the laryngeal region safe and feasible and with good surgical outcomes.